Drugie russkie . The Other Russian - Yusupova, Mayram (Russia, 2006)
Verzio FF submission The Other Russians depicts the- often forced- departure of ethnic Russians from those Republics of the former Soviet Union in which they formed a minority.This film sets out to represent the history of the non-Russian Russians in their accounts of this time- despite the continued silence of the Russian government and the governments of the independent former Soviet Central Asian states from which they were driven into exile.